Екоморфи технозему Нікопольського марганцеворудного басейну - Задорожна, Галина; Zadorozhnaya, Galyna (Східноєвропейський національний університет імені Лесі Українки, 2016)
Досліджено просторову варіабельність твердості педозему на ділянці рекультивації Нікопольського марганцеворудного басейну за регулярною сіткою (105 точок). Виконано екоморфічний аналіз рослинності. Установлено ступінь просторової залежності показників твердості досліджуваного ґрунту пошарово через кожні 5 см на глибину 50 см. Побудовано карти просторового розподілу показників твердості технозему за шарами. Спряженість варіацій зовнішніх ознак із просторовою гетерогенністю ґрунту підтверджує екологічний характер формування виявлених ґрунтових структур – екоморф – та дає можливість їх змістовного опису. The spatial variability of the mechanical impedance of the pedozem have been investigated within a regular grid (105 points) in Nikopol manganese ore basin polygon. Ecomorphic analysis of the vegetation in each cell of the grid has been done. The degree of spatial dependence of soil mechanical impedance in each layers from 5 cm to a depth of 50 cm have been assessed with the help of geostatistical analysis based on variogram. Maps of the spatial distribution of the tehnozem mechanical impedance have been plotted. Cluster analysis, conducted on the basis of the statistical data allowed to distribute the existing changes in soil mechanical profiles in three clusters with characteristic for them, relative to the same type of dynamic properties. Environmental separation content of the soil plots on clusters studied using discriminant and variance analyzes. Externalities associated with certain soil profiles characteristic of variability of damping, total salt regime, thermal climate, light in community, cryoclimate, trophicity index in the plant community. Statistical significance of variations of external properties associated with the spatial heterogeneity within soil plots belonging to different clusters allows them to be meaningfully interpreted and confirms the formation of ecological nature of the identified soil structures – ecomorphs. The findings reveal some of the mechanisms of interaction between the soil as biogeocoenose component with other components, and outline an integrated picture of the processes occurring in it intermediary between the factors of soil formation and soil properties.
Eсomorphs Tehnozem of Nikopol Manganese Mining Basin
Keywords: твердість ґрунту; екологічні фактори; морфологічні елементи; soil penetration resistance; environmental factors; morphological features